Penerapan Prompt Untuk Meningkatkan Keterampilan Identifikasi Melodi Dan Ritme Sederhana Anak Berkebutuhan Khusus Usia 7-8 TahunDi Sekolah XYZ Jakarta - Janice Gouw; M.B. Rini Wahyuningsih (Mathematics Education Study Program, 2025)
This study aims to assess the implementation of physical and visual prompts in enhancing the skills of identifying melodies and rhythms in special needs children aged 7-8 years at XYZ School in Jakarta. This study involved four children attending a special music education class, who have difficulties in identifying melodies and rhythms on the piano. Using an action research method, the instruments used included questionnaires and a Likert scale evaluation rubric for quantitative data, as well as observations and anecdotal notes for qualitative data. The physical prompts used involved direct assistance to the participants' hands to guide them to the correct note positions, while the visual prompts consisted of visual cards displaying musical notation. Initially, the participants' ability to identify melodies and rhythms was 0%, categorized as 'Not Developed'. After two intervention cycles, the ability to identify melodies increased to 98.21% and simple rhythms reached 100%, both categorized as 'Developed as Expected'. These findings support the integration of physical and visual prompts into the curriculum of special schools and teacher training, to maximize the learning potential of special needs children. Further studies are recommended to help educators understand various types of prompts and their applications in a broader educational context.